Solubility of carbon dioxide in aqueous blends of 2-amino-2-methyl-1-propanol and piperazine - Tong,D; Maitland,GC; Trusler,MJP; Fennell,PS (Chemical Engineering Science, 2013)
In this work, we report new solubility data for carbon dioxide in aqueous blends of 2-amino-2-methyl-1-propanol (AMP) and piperazine (PZ). A static-analytical apparatus, validated in previous work, was employed to obtain the results at temperatures of (313.2, 333.2, 373.2, 393.2) K, and at total pressures up to 460 kPa. Two different solvent blends were studied, both having a total amine mass fraction of 30%: (25 mass% AMP+5 mass% PZ) and (20 mass% AMP+10 mass% PZ). Comparisons between these PZ activated aqueous AMP systems and 30 mass% aqueous AMP have been made in terms of their cyclic capacities under typical scrubbing conditions of 313 K in the absorber and 393 K in the stripper. The Kent–Eisenberg model was used to correlate the experimental data.